Development and Characterization of Needle‐type Ion‐selective Microsensors for in situ Determination of Foliar Uptake of Zn2+ in Citrus Plants. Issue 4 (4th December 2017) - Church, Jared; Armas, Stephanie M.; Patel, Parth K.; Chumbimuni‐Torres, Karin; Lee, Woo Hyoung
Abstract: For over a decade, the incidence of Huanglongbing (HLB) has grown at an alarming rate, affecting citrus crops worldwide. Current methods of nutrient therapy have little to no effect in alleviating symptoms of HLB, and scarce research has been put forth towards non‐destructive tools for monitoring zinc transport in citrus plants. Here, we have developed and characterized a solid contact micro‐ion‐selective electrode (SC‐μ‐ISE) for the determination of zinc transport in sour orange seedlings using a non‐invasive microelectrode ion flux estimation (MIFE) technique. The SC‐μ‐ISE displayed a 26.05±0.13 mV decade −1 Nernstian response and a LOD of (3.96±2.09)×10 −7  M. Results showed a significant Zn 2+ uptake in the leaves and roots of sour orange seedlings when bulk concentrations were higher than 5.99 mM. Above this concentration, a linear relationship between flux and bulk Zn 2+ concentration was observed. This relationship suggests passive diffusion may be a key mechanism for Zn transport into plants. Overall, this study is the first to use a Zn 2+ SC‐μ‐ISE for the determination of ion transport processes in plants. This novel tool can be used to further knowledge the effect of nutrient therapy and disease progression on HLB infected citrus plants. Abstract :